ANALISIS PENGARUH KAUSALITAS ANTARA EKSPOR, IMPOR DAN PERTUMBUHAN EKONOMI DI INDONESIA DAN THAILAND DENGAN MENGGUNAKAN PENDEKATAN VAR PERIODE 1980-2013 - Moch Ilham; Agustina Suparyati (Jurnal Ekonomi Trisakti, 2022)
This study aimed to examine the effect of causality between exports, imports and GDPdi Indonesia and Thailand and analyze models for both countries. There is no independent and dependent variables in this study. The sample used in this study is the variable export, import and GDP of Indonesia and Thailand with purposive sampling method. This research use analysis method Vector Auto Regression (VAR) with the aid of Eviews 8.0. Results from this study showed that the variables export, import and GDP each have a causal relationship between the three. Based on the test results VAR, according to the value of the lowest Akaike Indonesia is a model for the state GDP = f (Export, Import), while for Thailand the country is a model Import = f (GDP, exports).